Identifikasi dan Prediksi Zona Rawan Bencana Banjir di Daerah Pesisir Kecamatan Teluk Ambon Baguala - Aditya Ramadhan; Samsul Bahri; Warni Multi; Sitti Hafsa Kotarumalos; Resti Limehuwey (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Ambon City, located in the Maluku Province, is experiencing rapid development. This rapid development has resulted in an increasing number of areas that should absorb water being covered by roads and buildings, leading to a decrease in water absorption into the ground and frequent flooding in several areas around the coast. This is due to the drastic increase in rainwater volume, which exceeds the capacity of drainage channels (culverts) and ultimately leads to flooding in rivers. Identifying flood-prone areas is crucial for estimating the potential impact of flooding. The results can be one of the flood mitigation efforts in the area. Geographic Information Systems (GIS) can be a solution for obtaining information on identifying and predicting flood-prone areas by creating, transforming, and analyzing field observation data into maps that show flood-prone areas. In this study, various factors and variables were collected and adjusted with specific considerations drawn from multiple references and reference materials to identify and predict flood vulnerability in the area. The analysis indicates that 5.98% of the coastal area in Teluk Ambon Baguala District has a very high vulnerability to flooding, while 58.89% of the coastal area is characterized by a high level of vulnerability to flooding.